Penyuluhan Pemahaman Loyalitas Siswa, Kepuasan Siswa Dan Kualitas Pelayanan Sekolah - Arief Hadian; Emelia Rahmadany Putri Gami; Mhd Dani Habra (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Al-Ikhwan Middle School is an integrated Islamic middle school situated in Hamlet XIII-B, Jalan Location No. 38, Bangun Sari, Tanjung Morawa District, Deli Serdang Regency, North Sumatra Province. Al-Ikhwan Middle School is an integrated Islamic institution that follows the principles of Islamic education based on the Qur'an and the Sunnah. In a broad sense, this school is considered to meet general educational standards. Given the competitive nature of attracting students, a crucial factor for educational institutions, schools consistently strive to create appealing aspects that entice potential students to enroll. To boost the enrollment of new students at Al-Ikhwan Middle School, an approach to enhance student satisfaction and foster loyalty within the school is deemed essential. This can be achieved through conducting counseling sessions that underscore the significance of elevating student contentment and fostering allegiance to the institution.